SHOPEE COLLABORATION WITH AFFILIATES TO CREATE CONSUMER IMPULSE BUYING - Churin In; Risna Nur Ainia; Firza Agung Prakoso (STEBI Global Mulia Cikarang, 2023)
One of the platforms developing in Indonesia is